Transcriptional Responses Associated with Virulence and Defence in the Interaction between Heterobasidion annosum s.s. and Norway Spruce. - Karl Lundén; Marie Danielsson; Mikael Brandström Durling; Katarina Ihrmark; Miguel Nemesio Gorriz; Jan Stenlid; Frederick O Asiegbu; Malin Elfstrand (PLoS ONE, 2015)
Heterobasidion annosum sensu lato is a serious pathogen causing root and stem rot to conifers in the northern hemisphere and rendering the timber defective for sawing and pulping. In this study we applied next-generation sequencing to i) identify transcriptional responses unique to Heterobasidion-inoculated Norway spruce and ii) investigate the H. annosum transcripts to identify putative virulence factors. To address these objectives we wounded or inoculated 30-year-old Norway spruce clones with H. annosum and 454-sequenced the transcriptome of the interaction at 0, 5 and 15 days post inoculation. The 491,860 high-quality reads were de novo assembled and the relative expression was analysed. Overall, very few H. annosum transcripts were represented in our dataset. Three delta-12 fatty acid desaturase transcripts and one Clavaminate synthase-like transcript, both associated with virulence in other pathosystems, were found among the significantly induced transcripts. The analysis of the Norway spruce transcriptional responses produced a handful of differentially expressed transcripts. Most of these transcripts originated from genes known to respond to H. annosum. However, three genes that had not previously been reported to respond to H. annosum showed specific induction to inoculation: an oxophytodienoic acid-reductase (OPR), a beta-glucosidase and a germin-like protein (GLP2) gene. Even in a small data set like ours, five novel highly expressed Norway spruce transcripts without significant alignment to any previously annotated protein in Genbank but present in the P. abies (v1.0) gene catalogue were identified. Their expression pattern suggests a role in defence. Therefore a more complete survey of the transcriptional responses in the interactions between Norway spruce and its major pathogen H. annosum would probably provide a better understanding of gymnosperm defence than accumulated until now.